PRESPEKTIF HARUN NASUTION DALAM DUNIA PENDIDIKAN DAN RELEVANSINYA DENGAN DUNIA MODERN - Ida Ayu Larasati (CV. Adiba Aisha Amira, 2025)
Harun Nasution's thoughts on rational Islam have made a significant contribution to the renewal of Islamic thought in Indonesia, especially in the field of education. Harun Nasution prioritizes a rational approach in understanding Islamic teachings, which aims to balance revelation and reason in the process of religious thinking. Through this approach, he emphasizes the importance of using reason in understanding religious texts so that Islam can be relevant to the development of the times and the challenges of modernity. In the context of education, Harun Nasution's rational thinking encourages the creation of a critical, open, and inclusive Islamic education system.